2016
DOI: 10.1103/physreve.94.042213
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of coupled oscillators can enhance their synchronization

Abstract: The heterogeneity of coupled oscillators is important for the degree of their synchronization. According to the classical Kuramoto model, larger heterogeneity reduces synchronization. Here, we show that in a model for coupled pancreatic β-cells, higher diversity of the cells induces higher synchrony. We find that any system of coupled oscillators that oscillates on two time scales and in which heterogeneity causes a transition from chaotic to damped oscillations on the fast time scale exhibits this property. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For example, in a system where oscillators of similar frequency are spatially grouped, the network synchronization is optimal under weaker coupling regimes compared to systems with random spatial assignment of frequency (56). A recent modeling study using a coupled b-cell model showed that greater heterogeneity among b-cells increased synchronization (57). Thus, islet dysfunction after disruptions to Cx36 gap junction coupling, which can occur in several conditions linked to the development of diabetes (13,14,58), may be protected by spatially grouping cells of similar excitability and oscillation frequency.…”
Section: Spatial Organization Of Cell Heterogeneitymentioning
confidence: 99%
“…For example, in a system where oscillators of similar frequency are spatially grouped, the network synchronization is optimal under weaker coupling regimes compared to systems with random spatial assignment of frequency (56). A recent modeling study using a coupled b-cell model showed that greater heterogeneity among b-cells increased synchronization (57). Thus, islet dysfunction after disruptions to Cx36 gap junction coupling, which can occur in several conditions linked to the development of diabetes (13,14,58), may be protected by spatially grouping cells of similar excitability and oscillation frequency.…”
Section: Spatial Organization Of Cell Heterogeneitymentioning
confidence: 99%
“…Previous analyses of synchronization of nonidentical chaotic oscillators have focused mainly on cluster synchronization [7,8] and phase synchronization [9][10][11][12][13]. For example, oscillator heterogeneity has been shown to mediate relay synchronization [14][15][16] and to induce frequency locking by suppressing chaos [17][18][19][20]. Global chaos synchronization of nonidentical oscillators, on the other hand, has been explored mainly for strong coupling and small parameter mismatches [21][22][23][24], with an emphasis on the extent to which synchrony persists when the oscillators are slightly different [25,26].…”
mentioning
confidence: 99%
“…For example, for coupled oscillators in a chaotic regime, heterogeneity can suppress chaos, giving rise to more regular patterns [17]. In these studies, and numerous subsequent ones [20][21][22], disorder does not stabilize the system around an original synchronization orbit, but instead generates new behavior that is qualitatively different. However, it has been recently realized that certain oscillator heterogeneities can stabilize a synchronization orbit of the homogeneous system [23][24][25].…”
Section: Introductionmentioning
confidence: 95%